Analisis Dampak Globalisasi terhadap Perdagangan Internasional - Anishah Wulandari; Devita Maulidia Soleha; Rechal Wulandari (J-MAS (Jurnal Manajemen dan Sains), 2023)
This research was conducted to analyze the impact of globalization on knowledge of international trade. This study is a normative study by examining various literatures. The data analysis technique used is qualitative analysis and quality descriptions in the form of data, sentences and statements so that the data is easier to read and understand. The results of the analysis show that the factors influencing international trade are production (potential factors of production owned by a company), diversity of conditions (availability and quality of resources), and production (amount of goods a country can produce). Countries trade with each other for goods that these countries cannot produce themselves.